Ameliorasi Usaha Batu Piring Melalui Digital Marketing dan Pengendalian Risiko Keselamatan dan Kesehatan Kerja - Yuliati, Lilis; Komariyah, Siti; Adenan, Moh.; Istiyani, Nanik (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
In an effort to increase the Development Village Index (IDM), the University of Jember has issued the Decree of the Chancellor of the University of Jember Number: 4242/UN25/KL/2022 about Jember University Foster Villages, and making Sumberkalong one of the Foster Villages. Sumberkalong was also designated as an Entrepreneurial Village by LP2M UNEJ based on village potential mapping. For this reason, the Proposal Team held discussions with stone plate craftsmen, the village government, and the sub-district to offer the best solution to increase the village's potential. The purpose of the Service is to create a productive, safe, comfortable and healthy work environment by using appropriate technology and personal protective equipment and developing technology-based marketing patterns to increase product sales. Probangdebi is carried out using the Participatory Rural Appraisal (PRA) method. The results of the dedication were in the form of the delivery of business capital in the form of stone cutting tools or machines and personal protective equipment or occupational safety and health equipment to members of the stone plate craftsman group. In addition, it also provides assistance related to the marketing process of stone plates to encourage increased business income.